The map of bones - Mosse, Kate, 1961- (Mosse, Kate, 1961- Joubert Family chronicles, 2024)
Olifantshoek, 1688 When the violent Cape wind blows from the south-east, they say the voices of the unquiet dead can be heard whispering through the deserted valley. Suzanne Joubert, a Huguenot refugee from war-torn France, arrives in search of her cousin - the notorious she-captain and pirate commander Louise Reydon-Joubert - who landed at the Cape of Good Hope more than sixty years before, then disappeared without a trace. Franshhoek, 1862 Nearly one hundred and eighty years after Suzanne's perilous journey, another intrepid and courageous woman of the Joubert family - Isabelle Lepard - has journeyed to the small frontier town once known as Olifantshoek in search of her long-lost relatives. Intent on putting the women of her family back into the history books, she quickly discovers that the crimes and tragedies of the past still shadow the present. And now, Isabelle faces a race against time if she is to discover the truth, an escape with her life.--